On-Site Traffic Management Evaluation and Proposals to Improve Safety of Access to Workplaces - Jozef Paľo; Ondrej Stopka (Communications - Scientific letters of the University of Zilina, 2021)
Transport is a phenomenon currently used in almost every sector. That is why attention is to be paid to transport safety, which should not only be addressed in relation to situation in cities or urban areas, but it is also necessary to deal with transport safety in larger enterprises where motor traffic encounters non-motorized traffic. The authors elaborated a similar research study. The introductory two sections analyze the current situation in terms of identifying bottlenecks of the traffic organization on the industrial site and possible separation of motor from non-motorized traffic to ensure safe access to workplaces and improve safety of transport on the site. In the most important part of the study, the obtained results are presented, wherein the “load” of the individual entry and exit points is specified. Thereafter, based on the acquired data, particular solutions related to transport safety with appropriate discussion are proposed.